Effects of systemic challenges on agricultural development systems: a systematic review of perspectives - Enock Siankwilimba; Jacqueline Hiddlestone-Mumford; Md Enamul Hoque; Bernard Mudenda Hang’ombe; Chisoni Mumba; Oliver Jolezya Hasimuna; Sahya Maulu; Joseph Mphande; Gunawan Prayitno (Cogent Food & Agriculture)
Achieving measurably reduced greenhouse gas emissions by 2030 as a key sustainable development goal has often been overshadowed by systemic challenges in the agricultural agribusiness system. Although many studies have examined sustainable agriculture extension services, few have considered the effects of the war in Ukraine, the Israeli-Palestinian conflict, climate change, debt burdens, and the ongoing impact of COVID-19. To address this gap, a systematic literature review of literature from 2019 to 2023 was undertaken to analyze the effects of climate change, COVID-19, debt burdens, and the conflict in Ukraine on sustainable agriculture development and extension services. The Russian conflicts have significantly disrupted the global agricultural landscape, impacting food supplies, production, and consumption due to distribution constraints. The loss of agricultural and health workers through COVID-19 has compounded the challenges. Studies also highlight rising inflation rates in many nations, driving communities further into debt, hunger, and poverty, with a noted 5.6% increase in worldwide debt due to COVID-19 alone, and an estimated 9.2% of the world going hungry in 2022. These disruptions have worsened existing agricultural challenges in developing countries such as a decline of 61% in pollinator numbers due to temperature rises caused by climate change, and a loss of 4.1 million hectares of tropical primary forest in 2022, releasing 2.7 gigatonnes of carbon dioxide. In response to these complex challenges, leadership that fosters collaboration among stakeholders through private and public dialogue is crucial. This study examines sustainable agricultural development and resilient extension services amid global systemic challenges.